Choice of enterprise form: Spain, 1886-1936 - Timothy Guinnane; Susana Martinez-Rodriguez (Yale University, Economic Growth Center, 2015)
Economists have long neglected study of an important contractual decision, a firm's choice of legal form. Enterprise form shapes the relations among a firm's owners as well as many features of a firm's interactions with the rest of the economy. Using unusual firm-level data on Spain 1886-1936, we estimate nested logit models of the determinants of enterprise form choice. In 1919, Spain introduced a new enterprise form that compromised between partnerships and corporations, and displaced larger partnerships and smaller corporations. This Sociedad de Responsabilidad Limitada was especially important for small and median-sized enterprises whose owners were not related.
Keywords: K20; N43; N44; 330; Law and finance; law and economics; legal form of enterprise; Spanish economic history; limited partnership; limited-liability company